Boosting HER Performance of Pt-Based Catalysts Immobilized on Functionalized Vulcan Carbon by Atomic Layer Deposition - Luo, Wei; Gan, Jie; Huang, Zikun; Chen, Wenyao; Qian, Gang; Zhou, Xinggui; Duan, Xuezhi (Frontiers in Materials, 2019)
Development of cost-effective Pt-based electrocatalysts is of scientific and industrial importance for hydrogen evolution from water splitting. In this work, cost-efficient Pt-based catalysts, immobilized on functionalized Vulcan Carbon (VC) from hydrothermal treatment of Ru precursor and ethylene glycol solution, for hydrogen evolution reaction (HER) are elaborately constructed via an elegant and controllable atomic layer deposition (ALD) technique. More carboxyl groups on the functionalized VC are suggested as the anchor sites for Pt immobilization, which gives rise to the more Pt active sites, desirable Pt electronic properties and stronger Pt-support interaction. The resultant 7.1 wt% Pt-based composite catalyst exhibits remarkably boosted HER activity and stability than the commercial 20 % Pt/C catalyst. These insights could open up a new avenue for fabrication of cost-effective Pt/C HER catalysts based on ALD technique.